Research on NOx Emission Reduction Technologies and Simulation of Environmental Benefits for Gas-Fired Power Plants in China - Zhitan LIU; Xiuyong ZHAO; Yugang LI; Kai WANG (Zhongguo dianli)
Based on the current development status, regional distribution and NOx emission situations of gas-fired power plants in China and the future trend of the environmental protection policies for gas-fired power generation, this paper firstly expounds the necessity of further NOx emission reductions from gas-fired power plants. Secondly, it analyzes and compares the pros and cons as well as the application potentials of three NOx emission reduction control technologies, i.e., low nitrogen burners, SCR of waste heat boilers and external control. Then, the meteorological model MM5 and the air quality model CALPUFF are used to simulate the atmospheric environmental benefits in the scenario of the projected gas-fired power generation capacity in Jiangsu Province in 2020. The research results show that the NOx emissions from gas-fired power generation may and must comply with higher emission standards, which will be conducive to improving regional environmental air quality and taking full advantages of gas-fired power generation in environmental protection.